Resistance of the microorganisms isolated from surgical hospital environment to disinfectants - E. V. Anganova; N. F. Kryukova (Acta Biomedica Scientifica, 2016)
The article presents the results of the study of resistance of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Aspergillus fungi to disinfectants. The microorganisms were isolated from the surgical ward environment of Central District Hospital of Neryungri. All strains were sensitive to Lysoformin 3000. Most of the microorganisms were sensitive to Ecocide and Septodor (85,7 % and 71,4 % respectively). Only E. coli was resistant to these disinfectants. The microorganisms showed the highest resistance to Javelion. S. aureus and E. coli were resistant to Javelion. The most effective disinfectants against Aspergillus were 1% solution of Septabic, 0,2% solution of Vegasept, 0,4% solution of Septodor, 0,5% solution of Lysoformin 3000. The other disinfectants (Chlor-sept, Hypocloride and Alfadez forte) had lower fungicidal activity against Aspergillus.